Impacts of Varying Nitrogen Levels on Leaf length of Onion Varieties under Poplar Based Agroforestry System - Kumar, Rajesh; Ramchandra; Bhardwaj, Atul Kumar; Chandra, K.K. (Indian Forester, 2022)
Agroforestry systems play a vital role in increasing the production of the crops that help to improve the financial status of the farmer. The experiment was laid out in a Randomized Block Design (Factorial) with three replications and 12 treatments with and without a combination of three onion varieties and different levels of nitrogen fertilizer. The experiment consisted of twelve treatments, viz. V1 + N 0 kg, V1 + N 40 kg, V1 + N 80 kg, V1 + N 120 kg, V2 + N 0 kg, V2 + N 40 kg, V2 + N 80 kg, V2 + N 120 kg, V3 + N 0 kg, V3 + N 40 kg, V3 + N 80 kg, and V3 + N 120 kg. The results revealed that leaf length was found superior at a 120 kg N/h fertilizer level (V1 + N 120 kg) in the onion variety Nasik Red. The onion variety Nasik Red was determined to be the best variety, and 120 kg N ha-1 was determined to be the optimum dose for achieving maximum onion leaf length in a poplar-based agroforestry system.